The salt mines of Santa Maria and Peñol Blanco in the second half of the sixteenth century. Border, joint labor and territorial articulation (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyzes the territorial articulation process occurred from the discoveryand exploitation of various salt efflorescence near the northwestern Zacatecas andSan Luis Potosi in the second half of the sixteenth century. The commercialization ofsalt from the Salinas de Santa Maria and Salinas del Peñol Blanco, not only boostedmine production of Zacatecas and other areas such as Pachuca and Guanajuato, butin the same way, under this commercial momentum other compulsive mechanismswere Developer, aimed to regulate the transfer of indigenous workers enrolled inthe district of Tlaltenango. This comprehensive process, little studied, on the otherhand, allows us to understand how that throughout this period the salt extraction(necessary element for the amalgamation of silver by the method of patio) acquireda remarkable range of expertise and generated a territorial configuration process inthe Septentrion of the New Spain.
Keywords: Salinas de Santa Maria and Peñol Blanco; sixteenth and seventeenth centuries; distribution system; Tlaltenango; Real Hacienda